Reframing schizophrenia and autism as bodily self-consciousness disorders leading to a deficit of theory of mind and empathy with social communication impairments. (August 2019) - Tordjman, S.; Celume, M.P; Denis, L.; Motillon, T.; Keromnes, G.
Highlights: Prior studies suggest self-consciousness disorders in schizophrenia and autism. Schizophrenia and autism are neurodevelopmental disorders sharing social communication impairments. Bodily self-consciousness relies particularly on intermodal sensory perception. Altered/absent intermodal sensory integration would lead to bodily self-consciousness disorders in schizophrenia and autism. This would result in problems of self-other differentiation, leading to impaired social communication and a deficit of theory of mind and empathy. Abstract: Prior observations and studies suggest self-consciousness disorders in schizophrenia and Autism Spectrum Disorder (ASD), two neurodevelopmental disorders sharing social communication impairments. First, the relationships between schizophrenia and autism are explored regarding social communication impairments. Then, self-consciousness disorders in schizophrenia and autism are described and discussed in relation with impairments of body self leading to impairments of self-other differentiation, a deficit of theory of mind and empathy, and their consequences on social communication. Also, neurological dysfunction involved possibly in self-consciousness disorders in schizophrenia and autism is presented. In conclusion, a new model is proposed integrating results of studies presented here and stating the existence of bodily self-consciousness disorders in schizophrenia and autism associated with altered/absent intermodal sensory integration (especially visual-kinesthetic-tactile integration). This would result in problems of self-other differentiation, leading in turn to a deficit of theory of mind and empathy as well as social communication impairments. This model opens new perspectives to understand better self-consciousness disorders and social communication impairments in schizophrenia and ASD and to develop therapeutic strategies.